Millenarianism - Jayne Svenungsson (St Andrews Encyclopaedia of Theology, 2022)
The word ‘millenarianism’ is used narrowly to describe the idea, expressed in Rev 20:1–10, of a thousand-year kingdom of the saints before the last judgment, and broadly to describe general expectations of imminent radical betterment on Earth that this idea has sparked throughout Christian history. The term is generally considered to be synonymous and interchangeable with chiliasm; both concepts have the same etymology, deriving from the Latin and Greek words for one thousand. However, the term is used in varying and often ambiguous ways by different scholars and across different disciplines, thus any exact definition must be to some extent stipulative. A fruitful way to delimit the concept of millenarianism, as used in this article, is to define it as a subcategory of apocalypticism, which in turn can be defined as a subdivision of eschatology. While eschatology is a general term referring to doctrines about the last things, apocalypticism is a particular set of beliefs about the end of times, characterized by historical determinism, a conviction of an imminent crisis of the present age, and belief in the judgment of evil and triumph of the good. Apocalyptic beliefs and movements, in this broad sense, can be found throughout history and across religious and cultural boundaries (although especially in the Abrahamitic traditions). While millenarianism shares the characteristics of apocalypticism, it denotes a more specific belief in a period of peaceful intermission on Earth before the final judgment and the creation of a new heaven and earth. This belief may be combined with different ideas of whether Christ himself will inaugurate these wondrous times (premillenarianism) or whether he will come only at the end of the millennium (postmillenarianism), but all forms of Christian millenarianism draw, directly or indirectly, on ideas and imageries expressed in Rev 20:1–10 and a few other passages of the New Testament scriptures. Although ideas of a millennial reign can be found in other cultural contexts and mythologies, ‘millenarianism’ will be limited in this article to the broad and complex Wirkungsgeschichte of these biblical texts (for phenomenological usages of the term to denote more general salvatory beliefs and expressions in a cross-cultural perspective, see Landes 2011; Wessinger 2011 [part IV]). Millenarianism has been the subject of vast historical scholarship and debate, where emphasis is often placed on its political, social and cultural manifestations. Drawing on this research, this article focuses on the theological understandings of millenarianism throughout Christian history. After a brief discussion of the scriptural origins of the idea of a thousand-year reign, an overview will be given of the most significant theological turning points in the history of millenarianism. In the third section, the twentieth-century discussion of the relationship between millenarianism and modern-day political utopianism will be addressed, and finally, in the fourth section, a summary will be given of more recent engagement with millenarian motifs in various forms of political theology.